f o g ( x ) alg (g o f)

User Generated

parjzna12512

Mathematics

Question Description

f(x)=5x and g(x)= x+6

(f o g)(x)=

(g o f)(x)=

(f o g)(3)

Student has agreed that all tutoring, explanations, and answers provided by the tutor will be used to help in the learning process and in accordance with Studypool's honor code & terms of service.

Explanation & Answer

Thank you for the opportunity to help you with your question!

f(x)=5x

g(x)=x+6

(f o g)(x)=5x*(x+6)

=5x^2+30x


(g o f)(x)=(x+6)*5x

=5x^2+30x


(f o g)(x)=5x^2+30x

when x=3

(f o g)(3)=5(3)^2+30*3

=45+90

=135



hope you happy with my answer please don't forget to rate me and leave a comment.if you have any question please let me know i'll choose the best answer for you.thank you.see you soon again...:)

Please let me know if you need any clarification. I'm always happy to answer your questions.

fnpuvagun (127)
UCLA

Anonymous
I was struggling with this subject, and this helped me a ton!

Studypool
4.7
Trustpilot
4.5
Sitejabber
4.4